ORGANISATIONAL CULTURE AND EMPLOYEE PERFORMANCE IN DEPOSIT MONEY BANKS IN YENAGOA, BAYELSA STATE, NIGERIA - F. N. Kieriseiye; L. L. Gilbert (American Journals Publishing, 2025)
The study investigated organisational culture and employees’ performance of deposit money banks in Yenagoa, Bayelsa State, Nigeria using four objectives. This study employs a descriptive survey research design and utilizes a quantitative research method by distributing an online questionnaire through the use of Google Form.
Keywords: Core values, Employee efficiency, Employee learning, Organisational culture, Work behaviour.